Reboxetine for acute treatment of major depression: systematic review and meta-analysis of published and unpublished placebo and selective serotonin reuptake inhibitor controlled trials. (12th October 2010) - Eyding, Dirk; Lelgemann, Monika; Grouven, Ulrich; Härter, Martin; Kromp, Mandy; Kaiser, Thomas; Kerekes, Michaela F; Gerken, Martin; Wieseler, Beate
Abstract : Objectives To assess the benefits and harms of reboxetine versus placebo or selective serotonin reuptake inhibitors (SSRIs) in the acute treatment of depression, and to measure the impact of potential publication bias in trials of reboxetine. Design Systematic review and meta-analysis including unpublished data. Data sources Bibliographic databases (Medline, Embase, PsycINFO, BIOSIS, and Cochrane Library), clinical trial registries, trial results databases, and regulatory authority websites up until February 2009, as well as unpublished data from the manufacturer of reboxetine (Pfizer, Berlin). Eligibility criteria Double blind, randomised, controlled trials of acute treatment (six weeks or more) with reboxetine versus placebo or SSRIs in adults with major depression. Outcome measures Remission and response rates (benefit outcomes), as well as rates of patients with at least one adverse event and withdrawals owing to adverse events (harm outcomes). Data extraction and data synthesis The procedures for data extraction and assessment of risk of bias were always conducted by one person and checked by another. If feasible, data were pooled by meta-analyses (random effects model). Publication bias was measured by comparing results of published and unpublished trials. Results We analysed 13 acute treatment trials that were placebo controlled, SSRI controlled, or both, which included 4098 patients. Data on 74% (3033/4098) of these patients were unpublished. In the reboxetine versus placebo comparison, no significant differences in remission rates were shown (odds ratio 1.17, 95% confidence interval 0.91 to 1.51; P=0.216). Substantial heterogeneity (I 2 =67.3%) was shown in the meta-analysis of the eight trials that investigated response rates for reboxetine versus placebo. A sensitivity analysis that excluded a small inpatient trial showed no significant difference in response rates between patients receiving reboxetine and those receiving placebo (OR 1.24, 95% CI 0.98 to 1.56; P=0.071; I 2 =42.1%). Reboxetine was inferior to SSRIs (fluoxetine, paroxetine, and citalopram) for remission rates (OR 0.80, 95% CI 0.67 to 0.96; P=0.015) and response rates (OR 0.80, 95% CI 0.67 to 0.95; P=0.01). Reboxetine was inferior to placebo for both harm outcomes (P<0.001 for both), and to fluoxetine for withdrawals owing to adverse events (OR 1.79, 95% CI 1.06 to 3.05; P=0.031). Published data overestimated the benefit of reboxetine versus placebo by up to 115% and reboxetine versus SSRIs by up to 23%, and also underestimated harm. Conclusions Reboxetine is, overall, an ineffective and potentially harmful antidepressant. Published evidence is affected by publication bias, underlining the urgent need for mandatory publication of trial data.